Revisiting Shimizu et al. (2004): What do we know and what should we know about cross-border mergers and acquisitions? - Manuel Wiedemann; Dodo zu Knyphausen-Aufseß; Niko Ippendorf (Review of Managerial Science, 2024)
Cross-border mergers and acquisitions (M&A) constitute an important phenomenon due to their volumes, frequencies, and strategic relevance for business practice. Academia has recognized the phenomenon's importance and compiled a wide spectrum of research. However, to the best of our knowledge, research has not provided a consolidation of recent literature findings particularly focused on cross-border M&A (as opposed to domestic M&A) since the publication of Shimizu et al.'s review in 2004. With this article we intend to close this gap by identifying, categorizing, synthesizing, and integrating recent literature to better understand what we do as well as what we should know about cross-border M&A. Thereby, literature findings are examined and discussed according to three perspectives: cross-border M&A as a (1) market entry mode, (2) dynamic learning process, and (3) value creating strategy. Based on the review, future research needs and opportunities are elaborated, first by directly following the findings from the review of the three research streams, and subsequently by adopting an overarching view that takes into account recent developments in multinational enterprise theory into account and addresses the “grand challenges” currently facing modern societies.
Keywords: M16; L19; L21; L25; 650; Cross-border mergers and acquisitions (M&A); Market entry mode; Dynamic learning; M&A performance